UV‐induced DNA damage disrupts the coordination between replication initiation, elongation and completion. (20th January 2021) - Wendel, Brian M.; Hollingsworth, Suzanne; Courcelle, Charmain T.; Courcelle, Justin
Abstract: Replication initiation, elongation and completion are tightly coordinated to ensure that all sequences replicate precisely once each generation. UV‐induced DNA damage disrupts replication and delays elongation, which may compromise this coordination leading to genome instability and cell death. Here, we profiled the Escherichia coli genome as it recovers from UV irradiation to determine how these replicational processes respond. We show that oriC initiations continue to occur, leading to copy number enrichments in this region. At late times, the combination of new oriC initiations and delayed elongating forks converging in the terminus appear to stress or impair the completion reaction, leading to a transient over‐replication in this region of the chromosome. In mutants impaired for restoring elongation, including recA, recF and uvrA, the genome degrades or remains static, suggesting that cell death occurs early after replication is disrupted, leaving partially duplicated genomes. In mutants impaired for completing replication, including recBC, sbcCD xonA and recG, the recovery of elongation and initiation leads to a bottleneck, where the nonterminus region of the genome is amplified and accumulates, indicating that a delayed cell death occurs in these mutants, likely resulting from mis‐segregation of unbalanced or unresolved chromosomes when cells divide. Abstract : UV damage delays elongation but not initiation, creating transient chromosome imbalances that stress the completion process and lead to copy number imbalances during the recovery period. We show that lethality occurs soon after disruption in mutants impaired for restoring replication, whereas mutants impaired for completing replication undergo a delayed cell death, resulting from amplified and unresolved chromosome imbalances.